Effect of serving time on microbiological quality of food served (chicken dish and rice) during wedding banquet - Ahmad, Noor Aliza (University Tun Hussein Onn Malaysia Press, 2018)
Ayam masak merah (chicken in tomato sauce) and nasi minyak (flavoured ghee rice) are among the common dish served in Malay wedding banquet. The microbiological quality of these dishes becomes a concern when there was a food poisoning that caused four deaths after attending the wedding banquet. Therefore, the aim of this work is to investigate the microbiological quality of ayam masak merah and nasi minyak during the serving time (0, 1, 2, 3 and 4 hours) at the wedding banquet. The microbiological analysis were; total plate count (TPC), total coliform, Escherichia coli , Staphylococcus aureus, Bacillus cereus, Salmonella spp., and Listeria spp. The results showed that ayam masak merah has the highest count for TPC, total coliform, Escherichia coli, Staphylococcus aureus, but low count in Listeria spp. and Salmonella spp. was not detected. Highest TPC was observed at the first hour of serving time, 7.33 log CFU/g, while for total coliforms and Staphylococcus aureus was at the 4 hours of serving time, 7.44 log CFU/g and 7.27 log CFU/g respectively.